EP.FRI.32 Emotional Resilience and Bariatric Surgical Teams: a Priorityin the Pandemic. (28th October 2021) - Graham, Yitka; Mahawar, Kamal; Riera, Manel; Omar, Islam; Bhasker, Aparna; Wilson, Michael
Abstract: The infection control measures implemented as a result of COVID-19 led to a postponement of bariatric surgical procedures across many countries worldwide. Many bariatric surgical teams were in essence left without a profession, with many redeployed to other areas of clinical care and were not able to provide the levels of patient support given before COVID-19. As the pandemic continues, some restrictions have been lifted, with staff adjusting to new ways of working, incorporating challenging working conditions and dealing with continuing levels of stress. This article explores the concept of emotional labour, defined as 'inducing or suppressing feelings in order to perform one's work', and its application to multidisciplinary teams working within bariatric surgery, to offer insight into the mental health issues that may be affecting healthcare professionals working in this discipline.